Visitors’ Motivations, Satisfaction and Loyalty Towards Castro Marim Medieval Fair - Barbeitos, Iolanda Márcia; Valle, Patrícia Oom do; Guerreiro, Manuela; Mendes, Júlio (Journal of Tourism, Sustainability and Well-being, 2014)
The study tests the relationship between motivation, satisfaction, and loyalty using a structural equation model. Data have been collected through a questionnaire applied to visitors attending a local festival, Castro Marim Medieval Fair, which hosts every year between 45.000 and 60.000 visitors. Results show that satisfaction towards controlled variables of the event within the venue’s boundaries, such as animation, gastronomy, and handicraft, influences visitors’ overall satisfaction towards the event. On the other hand, they also reveal a direct relationship between overall satisfaction and loyalty. The study contributes to a better understanding of visitors’ behaviour and provides useful guidance to festival ideation and design.